The implantable loop recorder in children - Yeung, B; McLeod, K (Heart (British Cardiac Society), 2008)
Objective:To evaluate use of the implantable loop recorder in children.Setting:Royal Hospital for Sick Children, Glasgow, UK.Method:Retrospective study of children who had an implantable loop recorder between September 1998 and October 2005.Results:38 devices were implanted in 34 children. Median age at implantation 11.3 years (range 1.8–17.6); median follow-up period 15 months (range 2–58). The main presenting complaint was syncope in 26 (76.5%), seizures in 6 (17.6%) and palpitations in 2 (5.9%). After implantation, 19 (55.9%) patients had symptom recurrence. Of these, 11 were shown to have sinus rhythm during symptoms and 8 had an abnormal ECG. Four patients had asystole >3 seconds and were diagnosed with reflex asystolic syncope; 2 had polymorphic ventricular tachycardia. One patient who already had a diagnosis of long QT syndrome was shown to have ventricular ectopy during symptoms and β-blockers were increased. One patient had transient complete heart block during symptoms but refused a pacemaker. In almost half the patients (44.1%), symptoms resolved after implantation. Complications requiring removal of the device occurred in 6 (15.8%) implants.Conclusions:In children with syncope and palpitations, the implantable loop recorder appears to be an excellent method of effecting a “cure” in almost 50% of subjects. For those who remain symptomatic, it is successful in determining cardiac rhythm during symptoms, but the complication rate in children may be higher than that of adults.